Kinetics Of Isothermal Adsorption Of Β-Carotene From Crude Palm Olein Using Bentonite - . Muslich; Prayoga Suryadharma; R. Indri R. Hayuningtyas (Jurnal Teknologi Industri Pertanian, 2009)
The adsorption of β-carotene from crude palm olein by using bentonite was investigated. Another adsorbent, which is activated carbons was used as a reference. The adsorption process of β-carotene was done using a mixed reactor. The objectives of this research are to obtain the equilibrium condition and the value of kinetics parameters, which are adsorption rate constant (k) and activation energy (Ea) of isothermal adsorption of β-carotene from crude palm olein using bentonite and activated carbons.  The achievement of equilibrium condition was influenced by adsorption process temperature. Higher adsorption temperature led to faster equilibrium time, but give the different influence for the value of β-carotene concentration in olein (μg/ml) for each adsorbents. Bentonite showed a faster equilibrium time (minute) and lower β-carotene concentration in olein (μg/ml) than activated carbons. For both adsorbents used, Freundlich isotherm model showed a good fit to the adsorption of β-carotene. The adsorption rate constant (k) was ascend by the higher of adsorption temperature. The activation energy of adsorption (Ea) was determined as bentonite 74,28 kcal mol-1 and activated carbons 30,04 kcal mol-1. Value of activation energy (Ea) indicates that adsorption process of β-carotene from crude palm olein by using activated carbon is more effective than that of bentonite.Keywords : adsorption, β-carotene, crude palm olein, bentonite.